Synthesis of acetamides via oxidative C–C bond cleavage of ketones catalyzed by Cu‐immobilized magnetic nanoparticles. (23rd July 2020) - Yazdani, Elahe; Pazoki, Farzane; Salamatmanesh, Arefe; Nejad, Masoume Jadidi; Miraki, Maryam Kazemi; Heydari, Akbar
Abstract : Copper supported on magnetite nanoparticles modified with environmentally friendly ligand tricine was devised for synthesis of acetamides via C–C oxidative cleavage of ketones with amines. The catalyst was characterized using different techniques, including Fourier transform infrared, X‐ray diffraction, scannin electron microscopy, vibrating sample magnetometry, thermogravimetric analysis, and energy dispersive x‐ray spectroscopy. The protocol showed relatively high yields of acetamide products. Furthermore, the magnetic recovery of the catalyst rendered the overall process fast and efficient. It was used in the reaction for six consecutive cycles with negligible loss of catalytic activity. This research is the first report of application of magnetic nanocatalysts for synthesis of acetamides from ketones of low activity through a C–C bond cleavage strategy. Abstract : Copper (II) supported magnetite nanoparticles synthesized and characterized. High activity in c–c bond oxidative cleavage of ketones for acetamides synthesis. Recyclability by magnetic decantation in 6 consecutive cycles.